Pulmonary sarcoidosis. (June 2016) - Butler, Marcus W.; Keane, Michael P.
Abstract: Sarcoidosis can occur after genetically susceptible individuals have been exposed to unidentified environmental antigens. Diagnosis requires clinical evaluation, chest radiography, lung function testing, judicious tissue biopsy (endobronchial ultrasound now being a preferred method) and exclusion of other granulomatous disease. No long-term systemic therapy is usually needed for the common presentation of Löfgren's syndrome (bilateral hilar lymphadenopathy, erythema nodosum, transient iritis). Corticosteroids remain first-line therapy, indicated for all patients presenting with pulmonary infiltrates and impaired lung function, and for those with critical extrathoracic organ dysfunction or hypercalcaemia. Corticosteroid-sparing immunosuppressive agents such as methotrexate, azathioprine (both used off-label for sarcoid in the UK) or hydroxychloroquine is frequently needed to minimize drug toxicities. Certain anti-tumour necrosis factor-α agents, (infliximab, adalimumab; unlicensed use in the UK) sometimes have a useful niche role in refractory disease as a supplement to other therapies, with 18 fluorodeoxyglucose positron emission tomography increasingly useful in assessment of refractory disease. Methylphenidate can help sarcoidosis-related fatigue (unlicensed use in the UK). Pulmonary hypertension can complicate advanced pulmonary sarcoidosis, increasing the rate of mortality from various forms of sarcoid-related pulmonary vasculopathy. Treatment options include epoprostenol, sildenafil or bosentan. Lung transplantation is successful in end-stage fibrotic disease, but sarcoid granulomas can reoccur in the allograft, and fungal contamination of fibro-bullous cavities can confer an increased postoperative risk of systemic infection.